2021
DOI: 10.1111/jcmm.17147
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with mitochondrial dynamics sensitizes glioblastoma multiforme to temozolomide chemotherapy

Abstract: Glioblastoma multiforme (GBM) is the most malignant primary tumour of the nervous system (CNS), with a very poor prognosis. The progression-free survival of patients with this condition after diagnosis is 6.2-7.5 months; the median survival is 14.6-16.7 months [1][2][3] and the 5-year survival rate is only 10%. 4 The current standard therapy for GBM is the maximal surgical resection with postoperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Mitochondria plays an important role both in regulating cell bioenergy production and in therapeutic resistance. [22,23] Responsible for producing 95% of total cellular ATP through oxidative phosphorylation (OXPHOS) as well as for controlling cell death and survival, mitochondria are critical for cellular function. [23] Cellular bioenergy production comes from glycolysis and mitochondrial OXPHOS essential for cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria plays an important role both in regulating cell bioenergy production and in therapeutic resistance. [22,23] Responsible for producing 95% of total cellular ATP through oxidative phosphorylation (OXPHOS) as well as for controlling cell death and survival, mitochondria are critical for cellular function. [23] Cellular bioenergy production comes from glycolysis and mitochondrial OXPHOS essential for cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that VEGFR2 inhibition elevated mitochondrial biogenesis and increased OXPHOS respiration, resulting in suppressing cell proliferation and promoting cell apoptosis. There is an earlier report showing that temozolomide treatment increased mitochondria size and OXPHOS levels in glioblastomas and resulted in temozolomide resistance, and that the interruption of mitochondria fusion process downregulated OXPHOS level and sensitized GBM cells to temozolomide [37]. Thus, the impact of elevated OXPHOS levels for glioblastoma treatment may be complex.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was also observed for the expression of CD44 and CD133 in BCSCs (two well-established markers of stemness) after treatment with AZD5363. Some studies reported a possible direct correlation between increased mitochondrial fusion and the chemo-resistance of tumor cells (Wang et al, 2022 ). In our study, the IC 50 value of doxorubicin, a common chemo drug used against TNBC, was significantly lower when combined with AZD5363 on BCSCs.…”
Section: Discussionmentioning
confidence: 99%